Characterization of karonda (Carissa carandus) genotypes under Punjab conditions - BONS, HARSIMRAT K; PAUL, AMANDEEP (The Indian Journal of Agricultural Sciences, 2020)
Karonda is rich source of iron, ascorbic acid, anthocyanins and other antioxidants. As karonda fruit is astringent and sour in taste and not used for desert purpose. Both ripe and unripe karonda fruits are used to prepare various value added products. On the basis of chemical composition, ripe fruits were better with desirable characters, hence G-3 appears to be the best among all the tested karonda genotypes i.e. more total soluble solids, total soluble sugars, ascorbic acid, total soluble proteins and iron content with low acidity and phenols. While, the physical parameters, viz. fruit colour, fruit diameter, fruit length, seed number, seed weight and pulp weight were observed maximum in G-2 followed by G-3 genotypes which can be useful for processing industries for preparation of value added products.